Insights into asthmatic airway remodelling through murine models - AL HEIALY, SABA; MCGOVERN, TOBY K.; MARTIN, JAMES G. (Respirology (Carlton, Vic.), 2011)
ABSTRACT Asthma is a chronic disorder of the airways associated in many instances with structural changes of the airways, termed airway remodelling. Irritant and allergen‐induced murine models have been used to further understand the mechanisms of airway remodelling. The infiltration of the airways by inflammatory cells, such as T lymphocytes, mast cells, eosinophils, neutrophils and macrophages after repeated allergen challenges may be important effectors in the initiation and perpetuation of airway remodelling through the release of inflammatory mediators and growth factors. Interleukins‐4 and ‐13 have been widely studied in experimental models, and have been shown to play a significant role in airway remodelling. Recently, a role for Th17 cells has been established. Other mediators involved in this process are ligands of the epidermal growth factor receptor, matrix metalloproteases and cysteinyl leukotrienes. A better understanding of the mechanisms leading to airway remodelling in allergic diseases may lead to the identification of novel therapeutic strategies but validation in human subjects is required for potential targets.